Evaluating the Usability of Canva Among University Students in Pekanbaru Using the WEBUSE Method - Hidayat, Rahmat; Andriyani, Yanti; Husnah, Mirdatul; Sinaga, Irfan; Avelia, Ririn; Maisarah, Dina; Fentika, Winda; Wulandari, Nindya (Journal of Applied Informatics and Computing, 2025)
Canva is a design platform used to create social media graphics, presentations, posters, documents, and other visual content. This study aims to evaluate user satisfaction with the web-based version of Canva using the WEBUSE method, which covers four main aspects: Content, Organization and Readability, Navigation and Links, User Interface Design, and Performance and Effectiveness. Data were collected through an online questionnaire distributed to university students in the Pekanbaru area via WhatsApp and Instagram. A total of 65 respondents were obtained through the data collection and screening process. The evaluation results show that all aspects fall into the "Good" usability category, with the highest average score in User Interface Design (0.75) and the lowest in Performance and Effectiveness (0.70), resulting in an overall average score of 0.725. Therefore, Canva’s website is considered to have good usability according to user perceptions. This study is expected to serve as input for feature development and service quality improvement of Canva in the future.